Suitability of Kharif Crops to Agroclimatic Conditions of Jamnagar - Saksena, Asha; Bhargava, P N (Annals of Arid Zone, 2016)
Suitability of kharif crops for Jarpnagar district has been examined on the basis of the data on productivity of crops, rainfall, evaporation and soil characteristics. It is observed that Jamnagar has a safe crop growing season of 17 weeks from 24th to 40th standard week. Variation in average' yields of these crops has indicated that cotton crop is more adaptable to the agroclimatic variations than other crops. Performance of ground nut is better than that of bajra and jowar. Critical examination of weekly Moisture Availability Index (MAI) has shown that if there are 8 or more weeks with MAI > 50 during the entire crop season yields of crops are normal. A slight reduction of even one or two weeks results in a severe reduction in the yields of jowar and bajra and a mild reduction in ground nut yield. The yield of cotton is not significantly reduced till number of such weeks is 4 or less. Fitting of requirement and availability of soil moisture shows that' cotton and groundnut should be sown around 24th week and jowar and bajra around 26th week. Growing of cotton and groundnut should be encouraged in the district.